2002
DOI: 10.1046/j.1439-037x.2002.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Dynamics in Rice (Oryza sativa) Before and After Flowering Based on SPAD (Chlorophyll) Meter Monitoring and its Relation with Grain Yield

Abstract: The rice plant at any point in time is composed of leaves of physiologically dierent ages, so it follows that the leaves dier in their contributions to the growth of the whole plant and its grain yield. As the leaf chlorophyll content (Soil Plant Analytical Division value) is the best indicator of photosynthetic activity in rice, the chlorophyll content of rice before and after¯owering was determined in a weed management ®eld experiment on direct wet seeded rice. The results indicated that the leaf chlorophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 4 publications
(2 reference statements)
4
31
0
1
Order By: Relevance
“…O valor crítico estimado do índice SPAD ao longo do ciclo está abaixo do encontrado, 70,6, por Westerveld et al (2004), que foi determinado no estádio de início do aparecimento das cabeças do cultivar Atlantis. Os valores de níveis críticos com o medidor portátil SPAD-502 são variáveis, precisando ser ajustados para cada situação, como deficiência de nutrientes e condições ambientais (Spaner et al, 2005), variedade (Hoel, 2003) e estádio de crescimento da cultura (Ramesh et al, 2002).…”
Section: Resultsunclassified
“…O valor crítico estimado do índice SPAD ao longo do ciclo está abaixo do encontrado, 70,6, por Westerveld et al (2004), que foi determinado no estádio de início do aparecimento das cabeças do cultivar Atlantis. Os valores de níveis críticos com o medidor portátil SPAD-502 são variáveis, precisando ser ajustados para cada situação, como deficiência de nutrientes e condições ambientais (Spaner et al, 2005), variedade (Hoel, 2003) e estádio de crescimento da cultura (Ramesh et al, 2002).…”
Section: Resultsunclassified
“…These methods have been widely adopted in crop production and research to monitor plant N status. For example, great potential for saving N by managing fertilizer N by using LCC was reported in rice [42], while others found that the SPAD meter and NDVI measurements were superior to LCC in rice because biomass was a factor in the SPAD meter and NDVI measurements, but LCC reading was not closely related to biomass [43,44]. For other crops, like Chrysanthemum, it was indicated that NDVI values exhibited higher correlation with leaf N than SPAD and atLEAF readings [30], which was presumably due to the small leaves making it difficult to accurately determine which part of the leaf was being sensed for SPAD and atLEAF sensors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SPAD values of flag leaf are one index closely related with N content of leaf. Many reports found photosynthesis and grain yield could be affected by the SPAD value of flag leaf at grain filling stage (Ramesh et al, 2002;Jiang et al, 2012;Huang et , and it was reported that the reasonable SPAD value could improve yield, but it varied in different rice varieties. In this study, the SPAD value of flag leaf was about 27-34 at grain filling stage in early rice, and 32-36 in late rice.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was found that normalized difference vegetation index (NDVI), SPAD and LCC have been used successfully to assess grain yield through building their relationships with N content of leaf or plant population. At different growth stages, Ramesh et al (2002) found that the SPAD values at 79 days after rice sowing correlated well with the grain yield. And LCC has been used successfully to guide fertilizer N application in rice, wheat and maize.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation